Решить систему уравнений

0 голосов
32 просмотров

Решить систему уравнений


image

Алгебра (49 баллов) | 32 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

1)\frac{-3+\sqrt{21} }{6}+\frac{-3-\sqrt{21} }{6}=\frac{-3+\sqrt{21}-3-\sqrt{21}}{6}=\frac{-6}{6}=-1\\\\-\frac{b}{a}=-1\\\\a=b\\\\2)\frac{-3+\sqrt{21} }{6} *\frac{-3-\sqrt{21} }{6} =\frac{(-3+\sqrt{21})(-3-\sqrt{21})}{6*6}=\frac{(-3)^{2}-(\sqrt{21})^{2}}{36}=\frac{9-21}{36}=-\frac{12}{36}=-\frac{1}{3}\\\\\frac{c}{a}=-\frac{1}{3}\\\\c=-1\\\\a=b=3

(220k баллов)